Particulate matter pollution in an informal settlement in Nairobi: Using citizen science to make the invisible visible. (January 2020) - West, Sarah E.; Büker, Patrick; Ashmore, Mike; Njoroge, George; Welden, Natalie; Muhoza, Cassilde; Osano, Philip; Makau, Jack; Njoroge, Patrick; Apondo, William
Abstract: We used a citizen science approach to explore personal exposure to air pollution of selected informal settlement dwellers in Nairobi, Kenya. This paper presents the methods used, with the aim of informing others who wish to conduct similar work in the future, and some results, including policy impact. We used three interlinked methods: 1) a personal mobile exposure monitoring campaign in which individual workers used Dylos monitors to measure variations in their exposure to fine particulate matter (PM2.5 ) within the settlement over the course of a day, 2) a questionnaire conducted before and after the monitoring campaign to assess any changes in knowledge or attitude in the wider community, and 3) two workshops, which facilitated the citizen science approach and brought together members of the community, local policy makers and researchers. The three elements of the study provided the local community, policymakers and scientists with new insights into the challenges air pollution poses for human health in such settlements, and opportunities for exploring how to monitor, mitigate and avoid these pollutants using a citizen science approach. We found significant differences in PM2.5 exposure between individual workers that could be partially explained by spatial differences in concentration that we identified within the settlement. Residents of the informal settlement identified a number of sources that might explain these differences in concentration, although many residents perceived air quality to be good both indoors and outdoors. The workshops raised awareness of the issue of air pollution and brought together affected community members and local and national policy makers to discuss air pollution issues in Nairobi's informal settlements. As a result, a new knowledge exchange network, the Kenya Air Quality Network, of policy-makers, researchers and community members was formed with the aim to facilitate the improvement of air quality across Kenya. Highlights: Nairobi informal settlement dwellers applied co-created citizen science approach. Community members learned to monitor and reduce personal exposure to air pollution. Personal fine particulate matter (PM2.5 ) exposure varied by occupation of dwellers. Perception of local air quality varied slightly by level of knowledge on issue. Policymakers and other stakeholders were inspired to form Kenya Air Quality Network.